2006
DOI: 10.1016/j.geb.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of storable votes

Abstract: The storable votes mechanism is a method of voting for committees that meet periodically to consider a series of binary decisions. Each member is allocated a fixed budget of votes to be cast as desired over the multiple decisions. Voters are induced to spend more votes on those decisions that matter to them most, shifting the ex ante probability of winning away from decisions they value less and towards decisions they value more, typically generating welfare gains over standard majority voting with non-storabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The experiment was designed to evaluate how well storable votes do in the laboratory when the order of the agenda is controlled by a chair, even with inexperienced subjects who may be prone to errors. Previous experiments with storable votes found the voting mechanism remarkably robust to strategic errors: the theoretical welfare properties matched the experimental data very well, even when the subjects' actions deviated systematically from equilibrium strategies (Casella et al, 2006. Evaluating the welfare implications of strategic mistakes is very difficult in theory, not least because the mistakes themselves are difficult to predict.…”
Section: Strategiesmentioning
confidence: 72%
See 1 more Smart Citation
“…The experiment was designed to evaluate how well storable votes do in the laboratory when the order of the agenda is controlled by a chair, even with inexperienced subjects who may be prone to errors. Previous experiments with storable votes found the voting mechanism remarkably robust to strategic errors: the theoretical welfare properties matched the experimental data very well, even when the subjects' actions deviated systematically from equilibrium strategies (Casella et al, 2006. Evaluating the welfare implications of strategic mistakes is very difficult in theory, not least because the mistakes themselves are difficult to predict.…”
Section: Strategiesmentioning
confidence: 72%
“…First proposed in Casella (2005) and studied experimentally in Casella et al (2006Casella et al ( , 2008, storable votes resemble Cumulative Voting, a voting system used in US corporate boards and local jurisdictions and allowing voters to spread freely across multiple candidates a given total budget of votes. Cumulative voting is designed to increase the representation of minorities (Guinier, 1994;Issacharoff et al, 2002), and has been shown to do so effectively, theoretically (Cox, 1990), empirically (Pildes and Donoghue, 1995;Bowler et al, 2003) and experimentally (Gerber et al, 1998).…”
mentioning
confidence: 99%
“… 6 See Schram and Sonnemans (1996), Morton and Williams (1999), Hung and Plott (2001), Goeree and Holt (2005), Großer and Schram (2006), Casella, Gelman and Palfrey (2006), Levine and Palfrey (2007), and Battaglini, Morton and Palfrey (2006) among others. …”
mentioning
confidence: 99%
“…We address this question in a companion experimental paper (Casella et al, 2003). The experimental subjects did not, for the most part, cast the equilibrium number of votes, but they consistently did cast more votes when intensities were higher.…”
Section: Discussionmentioning
confidence: 96%